Hormones and transport systems - Litwack, Gerald; Aghazadeh, Yasaman (Vitamins and hormones, 2015)
First published in 1943, Vitamins and Hormones is the longest-running serial published by Academic Press. The Series provides up-to-date information on vitamin and hormone research spanning data from molecular biology to the clinic. A volume can focus on a single molecule or on a disease that is related to vitamins or hormones. A hormone is interpreted broadly so that related substances, such as transmitters, cytokines, growth factors and others can be reviewed. This volume focuses on hormone and transport systems. Expertise of the contributors Coverage of a vast array of subjects In depth current information at the molecular to the clinical levels.